Sistem Proteksi Kebocoran Gas LPG Berbasis Arduino dan Aplikasi Mobile - Robertus Yunico Prasetiyo; Henry Novianus Palit; Resmana Lim (Jurnal Infra, 2019)
Until now there are still many people who do not know how to improve, and how to care for them. LPG in homes. Therefore we need a tool that can tell through the application if there is an accurate and fast LPG gas leak.Arduino and applications are made using LPG gas based on PPM levels in LPG tubes, and can also use LPG tube temperature and humidity that change suddenly in a certain period of time. If a leak occurs, the gas application will immediately notify you of the LPG leak.Based on the results of testing that has been done, Arduino can protect gas leaks through PPM levels and can also protect gas leakage through temperature and humidity. Arduino can also directly turn off LPG gas by turning the regulator knob to the off position. Arduino and applications can run properly according to their functions. The application can also provide notifications in the event of a gas leak.